Chronic Obstructive Pulmonary Disease in Non-smokers: A Case-Comparison Study. (1st February 2014) - Sexton, Paul; Black, Peter; Wu, Lian; Sommerville, Fay; Hamed, Maye; Milne, David; Metcalf, Patricia; Kolbe, John
Abstract Background: COPD is often regarded as a smoker's disease. In fact, up to 50% of COPD could be attributable to other causes. Relatively little is known about COPD among nonsmokers, and this group is usually excluded from studies of COPD. Methods: In this cross-sectional case-comparison study, smokers and nonsmokers aged over 45 with COPD (post-bronchodilator FEV1 ≤ 70% predicted, FEV1/FVC ratio < 0.7) were recruited from specialist outpatient clinics and from primary care. Subjects completed a questionnaire and interview, and underwent spirometry, venesection, exhaled nitric oxide (ENO) measurement, allergen skinprick testing, formal lung function testing and high resolution CT. Results: 48 nonsmokers and 45 smokers participated. Asthma was nearly universal among nonsmokers and was the commonest identifiable cause of COPD in that group. Nonsmokers also exhibited a high prevalence of objective eosinophilic inflammation (raised ENO and eosinophil counts, positive skinprick tests). Smokers had more severe airflow obstruction, but respiratory symptom prevalences were similar between groups. Nonsmokers reported greater lifetime burdens of respiratory disease. Nonsmokers' HRCT results showed functional small airways disease, with no significant emphysema in any subject. Previously undiagnosed bronchiectasis was common in both groups (31% and 42%). Conclusions: Asthma is a very common cause of COPD among nonsmokers. Radiological bronchiectasis is common in COPD; the clinical significance of this finding is unclear.